ANALISIS POLA SELEKSI, GRADASI, PRESENTASI DAN REPETISI KITÂB QOWÂ’ID AL-LUGHOH AL-‘ARABIYYAH KARYA MUHAMMAD YUSRON TAHUN 2022 - Asiyah, Dewi; Akhas, Muhammad Zayinil (Lugatuna : Jurnal Prodi PBA, 2024)
This research is based on the existence of a theory of material analysis offered by William Francis Mackey, which the author examined by looking at the teaching materials of the book "Qowȃ'id Al-Lughoh Al-'Arabiyyah" as a comparison of material analysis, the reason the author took this book, because this book is a textbook aimed at students, especially at UIN KH. Abdurrahman Wahid Pekalongan in the learning stages in lectures. Based on the background of the problem above, the problems can be formulated as follows: how is the suitability of the selection of material for the book "Qowȃ'id Al-Lughoh Al-'Arabiyyah" by Muhammad Yusron in 2022?, how is the suitability of the gradation of the material for the book "Qowȃ'id Al-Lughoh Al-'Arabiyyah" by Muhammad Yusron in 2022?, how is the suitability of the presentation of the material for the book "Qowȃ'id Al-Lughoh Al-'Arabiyyah" by Muhammad Yusron in 2022?, how is the suitability of the repetition of the material for the book "Qowȃ'id Al-Lughoh Al-'Arabiyyah" by Muhammad Yusron in 2022?. This study aims to analyze the quality of the book "Qowȃ'id Al-Lughoh Al-'Arabiyyah" based on Mackey's textbook compilation theory in terms of selection (selection of material), gradation (organization of material), presentation (presentation of material) and repetition (sharpening of material) in the book. This study uses a type of library research (Library Research) and the approach used is a qualitative approach. Data collection techniques use documentary study techniques or data collection techniques through documents, journal notes, books, theses and others obtained from libraries that contain the information sought to then be classified according to the research object needed. The data analysis technique in this study uses content analysis. The results of this study show similarities with the theory put forward by William Francis Mackey, namely that it has fulfilled (1) good selection, because the arrangement of the material is in accordance with the objectives, the level of student proficiency and the length of a language learning program, (2) good gradation, because the presentation of the material prioritizes simple rules that are more useful than complex rules, (3) the presentation used in the material is a differential procedure, an intensive procedure, a pictorial procedure and a context procedure, and (4) repetition is found in the form of repetition of reading skills and writing skills.